Novel poly(l‐lactide‐co‐caprolactone)/gelatin porous scaffolds for use in articular cartilage tissue engineering: Comparison of electrospinning and wet spinning processing methods. Issue 8 (28th September 2016) - Kalaithong, Wichaya; Molloy, Robert; Theerathanagorn, Tharinee; Janvikul, Wanida
Abstract : Some novel polymeric fibrous nonwoven meshes have been processed from solution blends of poly(l ‐lactide‐ co ‐caprolactone), P(LL‐CL), and gelatin for use as biodegradable porous scaffolds in articular cartilage tissue engineering. P(LL‐CL) copolymers with LL:CL compositions ranging from 50:50 to 80:20 mol% were synthesized via the bulk ring‐opening copolymerization of L‐lactide (LL) and ε‐caprolactone (CL) using tin(II) octoate, Sn(Oct)2, as the initiator. To make the hydrophobic P(LL‐CL) more hydrophilic for cell culture, it was solution blended with gelatin using trifluoroethanol as a common solvent to give P(LL‐CL):gelatin contents in the final scaffolds ranging from 70:30 to 95:5 wt%. Two different processing methods were used: electrospinning and wet spinning. Although electrospinning gave a more uniform mesh of nanosized fibers, the nonwoven mesh from wet spinning with its much larger pores and greater pliability was found to be more suitable for water absorption, cell infiltration and shape‐forming. Scanning electron micrographs of the scaffolds from the two techniques are compared. From the results obtained, the wet‐spun P(LL‐CL)50:50/gelatin 95:5 scaffold gave the best combination of properties. In particular, the 5% gelatin content resulted in a fivefold increase in the scaffold's equilibrium water uptake from about 10% to over 50% by weight. POLYM. ENG. SCI., 57:875–882, 2017. © 2016 Society of Plastics Engineers